2015
DOI: 10.1109/jmems.2015.2393858
|View full text |Cite
|
Sign up to set email alerts
|

Modal Parameter Tuning of an Axisymmetric Resonator via Mass Perturbation

Abstract: Abstract-This paper reports the permanent frequency mismatch reduction of the primary wineglass modes in a planar axisymmetric resonator by strategic mass loading. The resonator consists of a set of concentric rings that are affixed to neighboring rings by a staggered system of spokes. The outer layers of spokes are targets for mass deposition. The paper develops modified ring equations that guide the mass perturbation process and despite the fact that the deposited mass and deposition locations are quantized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…The innermost large spoke layer is designated as the first layer (i = 1) and the outermost spoke layer is designated as the fourth layer (i = 4). The resonator is a modification of the design described in [3]. The reader is referred to this paper for information on the resonator fabrication, electrode layout, test procedure, and the process for extracting pertinent modal parameters from empirical frequency response data.…”
Section: A Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…The innermost large spoke layer is designated as the first layer (i = 1) and the outermost spoke layer is designated as the fourth layer (i = 4). The resonator is a modification of the design described in [3]. The reader is referred to this paper for information on the resonator fabrication, electrode layout, test procedure, and the process for extracting pertinent modal parameters from empirical frequency response data.…”
Section: A Backgroundmentioning
confidence: 99%
“…In this report the resonator is fabricated without the gold film on, or the reservoirs in, the large spokes. Consequently, these areas are targets for further etching in order to selectively remove material from the resonator instead of adding material as was pursued in [3]. It will be shown that material removal at the large spokes locations does not modify the stiffness properties of the resonator and so models that readily predict the changes in the resonator modal properties can be developed by assuming only the mass distribution is perturbed.…”
Section: A Backgroundmentioning
confidence: 99%
See 3 more Smart Citations